Sight unseen a novel - Johansen, Iris; Johansen, Roy
"Someone is killing people in ways that mirror Kendra Michaels's most notorious cases and Kendra must come face to face with her most ruthless enemy"--
Keywords: Traffic accident investigation; Women -- Psychic ability; Large type books; Paranormal fiction; Large type books; Suspense fiction; Mystery fiction; Fiction